Preferential location of lidocaine and etidocaine in lecithin bilayers as determined by EPR, fluorescence and H-2 NMR - de Paula, Eneida; Schreier, Shirley; Jarrell, Harold C.; Fraceto, Leonardo Fernandes (Elsevier B.V., 2008)
We have examined the effect of the uncharged species of lidocaine (LDC) and etidocaine (EDC) on the acyl chain moiety of egg phosphatidylcholine liposomes. Changes in membrane organization caused by both anesthetics were detected through the use of EPR spin labels (5, 7 and 12 doxyl stearic acid methyl ester) or fluorescence probes (4, 6, 10, 16 pyrene-fatty acids). The disturbance caused by the LA was greater when the probes were inserted in more external positions of the acyl chain and decreased towards the hydrophobic core of the membrane. The results indicate a preferential insertion of LDC at the polar interface of the bilayer and in the first half of the acyl chain, for EDC. Additionally, 2 H NMR spectra of multilamellar liposomes composed by acyl chain-perdeutero DMPC and EPC (1:4 mol%) allowed the determination of the segmental order (S-mol) and dynamics (T-1) of the acyl chain region. In accordance to the fluorescence and EPR results, changes in molecular orientation and dynamics are more prominent if the LA preferential location is more superficial, as for LDC while EDC seems to organize the acyl chain region between carbons 2-8, which is indicative of its positioning. We propose that the preferential location of LDC and EDC inside the bilayers creates a "transient site", which is related to the anesthetic potency since it could modulate the access of these molecules to their binding site(s) in the voltage-gated sodium channel. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: local anesthetic; membrane; fluorescence; magnetic resonance; liposomes